The attachment process of rocket‐triggered lightning dart‐stepped leaders. Issue 2 (29th January 2016) - Hill, J. D.; Uman, M. A.; Jordan, D. M.; Ngin, T.; Gamerota, W. R.; Pilkey, J.; Caicedo, J.
Abstract: Time‐correlated 1.54 µs high‐speed video frames, channel‐base current and current derivative (d I /d t ), and electric field derivative (d E /d t ) measurements are used to analyze the attachment process of triggered lightning dart‐stepped leaders. Lengths, speeds, and durations of the upward‐connecting positive leaders propagating from the launching structure are measured and calculated. The "leader burst" occurring immediately preceding the d E /d t slow front is demonstrated to be a distinctly different process from the preceding downward dart‐stepped leader steps and is associated with the fast increase in channel‐base current due to the initial interactions of the downward and upward leader streamer zones. Locations of the leader burst pulses are found to occur within or immediately above the connection region. Pulses superimposed on the d E /d t slow front are shown to occur after the initial connection between the downward and upward leaders and are associated with kiloampere‐scale increases in the channel‐base current. Subsequent fast‐transition pulses are found to produce multiple kiloampere‐scale increases in the channel‐base current. Observed time delays between d E /d t and d I /d t peaks for slow front and fast‐transition pulses confirm the existence of an elevated junction point between the downward and upward leaders. Average downward current wave speeds for fast‐transition pulses are found to be a factor of 2 to 2.5 faster than those for slow‐front pulses. For 51 dart‐stepped leader events, the average total duration of the attachment process, starting with the initial fast current increase and ending with the peak of the final d I /d t fast‐transition pulse, is measured to be 1.77 µs. Key Points: In‐depth analyses of the attachment process of triggered lightning dart‐stepped leaders Lengths, speeds, and durations of the upward connecting positive leader are measured and calculated Observed time delay between d E /d t and d I /d t peaks confirms existence of elevated junction point